Unraveling the dynamic transcriptomic changes during the dimorphic transition of Talaromyces marneffei through time-course analysis - Du, Minghao; Tao, Changyu; Hu, Xueyan; Zhang, Yun; Kan, Jun; Wang, Juan; Yang, Ence (Frontiers in Microbiology, 2024)
Systemic dimorphic fungi pose a significant public health challenge, causing over one million new infections annually. The dimorphic transition between saprophytic mycelia and pathogenic yeasts is strongly associated with the pathogenesis of dimorphic fungi. However, despite the dynamic nature of dimorphic transition, the current omics studies focused on dimorphic transition primarily employ static strategies, partly due to the lack of suitable dynamic analytical methods. Here, we firstly conducted time-course transcriptional profiling during the dimorphic transition of Talaromyces marneffei, a model organism for thermally dimorphic fungi. Then, we identified 5,223 dimorphic transition induced genes (DTIGs) by developing DyGAM-NS (dynamic optimized generalized additive model with natural cubic smoothing), a model that enables the capture of non-uniform and nonlinear transcriptional changes during intricate biological processes. Notably, the DyGAM-NS model showcases performance on par with or superior to other commonly used models, achieving the highest F1 score in our assessment. Moreover, the DyGAM-NS model also demonstrates potential in predicting gene expression levels throughout temporal processes. The cluster analysis of DTIGs suggests differential functional involvement of genes at distinct stages of dimorphic transition. Moreover, we observed divergent gene expression patterns between mycelium-to-yeast and yeast-to-mycelium transitions, indicating the asymmetrical nature of two transition directions. Additionally, leveraging the identified DTIGs, we constructed a regulatory network for the dimorphic transition and identified two zinc finger-containing transcription factors that potentially regulate dimorphic transition in T. marneffei. In summary, our study not only elucidates the dynamic changes in transcriptional profiles during the dimorphic transition of T. marneffei but also provides a novel perspective for unraveling the underlying mechanisms of fungal dimorphism.